Using cytometric bead arrays to detect cytokines in the serum of patients with different types of pulmonary tuberculosis. (April 2019) - Bai, Ruolan; Tao, Luyan; Li, Bingxue; Liu, Aihua; Dai, Xiting; Ji, Zhenhua; Jian, Miaomiao; Ding, Zhe; Luo, Lisha; Chen, Taigui; Ma, Mingbiao; Peng, Yun; et al.
Cytokines play a crucial role in mediating immune responses to tuberculosis (TB). The aim of this study was to evaluate the levels of cytokines in patients with different forms of pulmonary tuberculosis (PTB) and identify valuable cytokine biomarkers for the diagnosis of PTB. We measured the levels of six cytokines (interleukin (IL-2, IL-4, IL-6, and IL-10), tumor necrosis factor (TNF-α), and interferon-γ (IFN-γ)) in the serum of healthy donors (n = 30). Patients with active PTB (n = 46) and those with latent tuberculosis infection (LTBI, n = 38) were examined using cytometric bead arrays. The levels of the six cytokines in the serum samples were measured promptly, sensitively, and simultaneously. The levels of IL-2, IL-6, IL-10, and IFN-γ were significantly higher in the PTB group compared with those reported in the healthy donors ( P  < 0.01 or P  < 0.05). In addition, significantly higher levels of IL-2, IL-6, IL-10, and IFN-γ were found in the active PTB group compared with those observed in the LTBI group ( P  < 0.01 or P  < 0.05). However, the levels of IL-4 and TNF-α in the sera of patients from the PTB group did not show a significant correlation with those measured in the healthy donor group. Our data demonstrated that IL-2, IL-6, IL-10, and IFN-γ may be useful in the auxiliary diagnosis of tuberculosis and as biomarkers for distinguishing LTBI from TB.